Effects of singing on vascular health in older adults with coronary artery disease: a randomized, crossover trial - Bagherimohamadipour, Mehri; Hammad, Muhammad; Visotcky, Alexis; Sparapani, Rodney; Kulinski, Jacquelyn (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe impact of singing on cardiovascular health has not been extensively studied. The aim of this study is to investigate the effect of singing on cardiovascular biomarkers in an aging population with coronary artery disease (CAD).MethodsParticipants had three study visits separated by 2–7 days, according to a randomized, researcher-blinded, crossover, controlled design: (1) a 30-min period of live singing with an in-person music therapist, (2) a 30-min period of singing along to an instructional video and (3) a 30-min rest (control). Primary outcomes included macrovascular endothelial function assessed by brachial artery flow-mediated dilation and microvascular function assessed by peripheral arterial tonometry [Framingham reactive hyperemia index (fRHI) and reactive hyperemia index (RHI)]. Heart rate variability (HRV) was a secondary outcome.ResultsSixty-five subjects (mean age 67.7 ± 0.8 years, 40% female) completed the study. Compared to control, there was an increase in fRHI for the singing video intervention (estimate: 0.54, SE: 0.19, p = 0.005) but not for the live singing intervention (estimate: 0.11, SE: 0.18, p = 0.570). There was no change in macrovascular function with either intervention. The low frequency/high frequency (LF/HF) ratio increased by 2.80 (SE: 1.03, p = 0.008), and the natural logarithm of high frequency (LnHF) power decreased by −0.90 ms2 (SE: 0.29, p = 0.003) with the video (during to pre-change). When assessing post- to pre- change, the live singing intervention showed a significant change of −0.62 ms2 (SE 0.29, p = 0.036) in LnHF power.ConclusionsSinging along to an instructional video for 30 min improved microvascular, but not macrovascular, endothelial function, in older patients with CAD. HRV changes with singing are similar to that of exercise. Clinical trial registrationClinicalTrials.gov, identifier (NCT04121741).